The Challenges of Transport and Egyptian Women’s Participation in the Job Market - Abo Shady, Radwa (AUC Knowledge Fountain, 2021)
This thesis aims to explore the effect of transportation on development in general and as a barrier to women’s contribution to the labor market in particular. A survey using a mixed method was filled online by working women in Egypt about their trip and perception about the transport problems. A framework was created to describe the relationship between different factors affecting women’s options. The findings suggested that transport parameters have an impact on the freedom of transport and eventually the final decision to join the labor market. The findings match the literature that transport should be gender-sensitive to empower women in the job market. Variables such as the time, age, marital status, and cost helps in understanding women’s decision to take public transport or not in their daily commute. Policymakers should take required actions to develop this sector for better female participation in the labor market.